9th Five Year Plan 1997-2002 Proposals Volume-I Sector: Agriculture and Allied Activities Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1997)
Planting materials imported from mainland are distributed to the cultivators at 20% cost subsidy. The department has established preservation unit with a view to demonstrate the farmers/Organisations about the preservation of fruits.
Andaman and Nicobar Administration, Planning Department